The Development of Science Education Research in Brazil and Contributions from the History and Philosophy of Science - Villani, Alberto; Dias, Valeria Silva [UNESP]; Valadares, Juarez Melgaco (Routledge Journals, Taylor & Francis Ltd, 2010)
Over the last 50 years a new research area, science education research, has arisen and undergone singular development worldwide. In the specific case of Brazil, research in science education first appeared systematically 40 years ago, as a consequence of an overall renovation in the field of science education. This evolution was also related to the political events taking place in the country. We will use the theoretical work of Rene Kaes on the development of groups and institutions as a basis for our discussion of the most important aspects that have helped the area of science education research develop into an institution and kept it operating as such. The growth of this area of research can be divided into three phases: The first was related to its beginning and early configurations; the second consisted of a process of consolidation of this institution; and the third consists of more recent developments, characterised by a multiplicity of research lines and corresponding challenges to be faced. In particular, we will analyse the special contributions to this study gleaned from the field known as the history and philosophy of science.
Keywords: History and philosophy of science; Institutional development; Kaes' model; Science education research